CONTRIBUTION OF LEARNING STYLES OF MECHANICAL ENGINEERING STUDENT LEARNING OUTCOMES STUDY PROGRAM STATE UNIVERSITY ENGINEERING EDUCATION BUILDING PADANG - 1848-1866 , Fandy Pratama (Universitas Negeri Padang, 2016)
ABSTRACTThis study aims to reveal the contribution of learning styles on learning outcomes of students of engineering mechanics of Technical Education Building. The hypothesis of this study is there is a contribution to the learning outcomes of learning styles of engineering mechanics students of Technical Education Building.This type of research is conducted at the Research Correlational Technical Education Building Study Program. These research subjects are students of Building Engineering Education in 2013 and 2014. The population in this research were 144 students. The sampling technique used was proportional random sampling totaling 106 students.The research findings are contained visual learning styles contribute to the learning outcomes of students of Engineering Mechanics Building Engineering Study Program. While audiotorial and kinesthetic learning styles are not contributing to the learning outcomes of students of Engineering Mechanics Building Engineering Study Program. Keywords: Contributions, Learning Styles, Learning Outcomes.